PENGGUNAAN LAGU DALAM PEMBELAJARAN BAHASA INGGRIS UNTUK SISWA SD; MENGAPA DAN BAGAIMANA - Nurhayati, Lusi (MAJALAH ILMIAH PEMBELAJARAN, 2009)
This article will describe the advantages of song to support Englishlanguage learning process and also review some methods to use songs in Englishclassroom. Moreover, this article will explain the position of English language inIndonesia and the characteristic of children as foreign language learners.Children have unique characteristics that could be employed for thesupporting factors and disadvantaging factors of foreign language learningprocess. They need to move, be able to concentrate for a short term, learningthrough experiences, less ability to control and plan their activities, not fear to dosome mistakes or take risks, not really paying attention to their shelves or theiractions, paying attention to the language purposes and possessing limitedexperiences in their lives. Songs are learning resources that have so manyadvantages, including linguistics resource, affective/psychological resource, andcognitive resource.Songs also can be used as a media to teach four major skills, which arespeaking, reading and writing. Another language skill such as pronunciation,vocabulary and grammar can be learnt wit the use of songs as well.Songs can be good learning sources for English language class. It wouldbe better if English language teachers in elementary schools realize the advantagesof using songs in the learning process to improve the quality of English languagelearning process. Using textbooks is no longer sufficient. Teachers are demandedto be creative in creating class activities to stimulate children so that they becomeinterested toward English language. Hence, their interests toward Englishlanguage would be an essential foundation to achieve the more satisfied Englishlanguage capability.